Languaging as competencing: considering language learning as enactment. Issue 1 (2nd January 2018) - Hellermann, John
Abstract: The terms interactional competence and learning are discussed in the context of recent research in the areas of cognitive science and ethnomethodological conversation analysis studies of language learning. Two data excerpts from a longitudinal case study of a beginning learner of English are presented to illustrate (1) the difficulty of representing language learning using structural linguistic representations and (2) evidence of language learning as at-that-time appropriate embodied interaction.